Hubungan Kadar Karbon Monoksida dalam Darah Pada Mahasiswa Universitas Mohammad Husni Thamrin dengan Perbedaan Usia, Jenis Kelamin, Kebiasaan Merokok dan Lama Perjalanan dengan Mengendarai Sepeda Motor - Kristianingsih, Yuli; Masdianto, Masdianto; Kurniawati, Yuyun; Ranggita, Amelia (Universitas Mohammad Husni Thamrin, 2024)
Carbon monoxide (CO) is a colorless, odorless and tasteless gas. Exposure to high and continuous concentrations of carbon monoxide gas can cause an increase in blood carboxyhemoglobin (COHb) levels, health problems and can even cause death. Motorcyclists are people who are often exposed to carbon monoxide continuously. The aim of this study was to determine carboxyhemoglobin levels in MH Thamrin University students who ride motorbikes. The qualitative research method uses the Conway cell diffusion method and quantitative uses a UV-VIS spectrophotometer to determine COHb levels in the blood. The sample used in this research was 30 students at MH Thamrin University, obtained using a quota sampling technique with specified criteria. The results of the Conway diffusion cell method test showed that there was no color change in the blood sample, while the UV-VIS spectrophotometer test results showed that the COHb level in the blood examined was no more than 3.5%. In conclusion, all samples examined still had levels below the normal threshold of PERMENKES RI No. 70 of 2016, namely no more than 3.5%. Keywords: Carboxyhemoglobin, Carbon Monoxide, Motorcycle Rider